Liability of operators of unmanned aerial vehicles for flight delays or cancellations (Ius Novum, 2021)
Unmanned aircraft, including flying models, are widely available and can be used by almost everyone. Despite the ban on operations with the use of drones in the area of airports, there are situations in which the irresponsible behavior of drone operators may cause an air accident or paralyze the airport, causing multi-million losses related to the cancellation and delay of flights. Passengers of these flights suffer various types of damage, including, for example, loss of connection (ticket cost), hotel expenses, hotel transport, meals, or even non-pecuniary damage consisting in suffering from the inability to spend holidays with family, etc. The question is who should be liable and pay compensation? This article aims to answer this question and indicate whether the cancellation of a flight due to the appearance of a drone over an airport is a so-called an extraordinary circumstance which would exempt the air carrier from its obligation to pay compensation.
Keywords: unmanned aerial vehicles; drones; drone laws; compensation for flight delays; extraordinary circumstances; Regulation 261/2004; airline passengers’ rights